Efficaciousness of dexmedetomidine in children undergoing cleft lip and palate repair: a systematic review and meta-analysis - Li Pan; Jiale Quan; Chunwei Lian; Dengfeng Liu; Yin Gao; Jiefan Liu; Xiangwei Li; Congcong Huang (BMJ Open)
Objective To systematically assess the efficacy and safety of dexmedetomidine as an anaesthesia adjuvant for cleft lip and palate (CLP) repair in children.Design Systematic review and meta-analysis.Data sources PubMed, Embase, Cochrane, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP) and Wanfang (up to October 2020). Studies in languages other than English and Chinese were excluded.Eligibility criteria for selecting studies Randomised controlled trials (RCTs) evaluating the impact of dexmedetomidine on emergence agitation (EA), the need for postoperative rescue analgesics, postoperative nausea and vomiting (PONV), and other adverse events in paediatric patients during CLP repair.Data extraction and synthesis The quality of evidence was assessed by using the Cochrane Review Methods and the Grading of Recommendations Assessment, Development and Evaluation approach. Data were screened, extracted and assessed by two independent authors. Outcomes were reported as a risk ratio (RR) with a 95% CI. A random-effect model was used when heterogeneity was detected.Results Thirteen studies including 1040 children met the inclusion criteria. The incidence of EA was significantly decreased in the dexmedetomidine group (RR, 0.19; 95% CI 0.10 to 0.36; p<0.00001; I2=56%) as compared with the control group. Paediatric patients receiving dexmedetomidine had lower postoperative analgesic requirements (RR, 0.27; 95% CI 0.10 to 0.73; p=0.01; I2=84%) and a lower incidence of respiratory adverse events (RR, 0.49; 95% CI 0.31 to 0.78; p=0.003; I2=0%). There were no significant differences in the risk of PONV and cardiovascular adverse events.Conclusions There was a lack of high-quality studies in this field. Perioperative administration of dexmedetomidine reduced the need for postoperative rescue analgesics and the incidence of EA in children without side effects undergoing CLP repair. However, further verification with larger samples and higher-quality RCTs is needed.